2005
DOI: 10.1080/14786430500157029
|View full text |Cite
|
Sign up to set email alerts
|

On the rigid to floppy transitions in calcium silicate glasses from Raman scattering and cluster constraint analysis

Abstract: To cite this article: M. Micoulaut , M. Malki , P. Simon & A. Canizares (2005) On the rigid to floppy transitions in calcium silicate glasses from Raman scattering and cluster constraint analysis, Philosophical Magazine, 85:28, 3357-3378, Calcium silicate glasses xCaO À (1 À x)SiO 2 exhibit a threshold in Raman lineshapes which can be related, on the basis of Maxwell constraint counting, to the onset of network rigidity as the concentration of calcium oxide x is decreased. The present results are more deeply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
(73 reference statements)
2
16
0
Order By: Relevance
“…A characterization of glasses by different experimental techniques in a range of compositions including this threshold is thus necessary to get a full picture of the structural changes. To our best knowledge, Raman spectroscopy was the only technique that has investigated this system in a large range of compositions [2][3][4][5][6][7][8][9][10][11][12][13]. Most of the other studies have been limited to a single composition, generally the calcium metasilicate one.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A characterization of glasses by different experimental techniques in a range of compositions including this threshold is thus necessary to get a full picture of the structural changes. To our best knowledge, Raman spectroscopy was the only technique that has investigated this system in a large range of compositions [2][3][4][5][6][7][8][9][10][11][12][13]. Most of the other studies have been limited to a single composition, generally the calcium metasilicate one.…”
Section: Introductionmentioning
confidence: 97%
“…Several papers investigating glass compounds of the calcium silicate system have shown that significant changes of physical properties take place around 45 mol% of CaO content [5][6][7][8]. Kalampounias et al [6] have attributed the structural evolution to a microphase separation near the peritectic composition of the binary system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…From a fundamental point of view, the very wide glass forming range of this glass system is also of great interest and was recently used to test a generalized formulation of the modified Urbach's rule (MRU) which is applicable to glassy materials [1]. In order to understand why this system can form glasses in a very large range of composition by comparison to alkaline earth silicate glass systems [2,3], numerous studies have been reported. The local structures of these compounds have been widely investigated by NMR [4][5][6][7][8], X-ray spectroscopy [8][9][10][11][12][13][14][15][16] and molecular dynamics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…From a fundamental point of view, the very wide glass forming range of this glass system is also of great interest and has recently been used to test the modified Urbach's rule (MRU) which is applicable to glassy materials [13]. This system can form glasses over a very large range of composition by comparison to alkaline earth silicate glass systems [14,15]. Some considerable efforts and conflicting views have been given to explain the composition dependence of the structure and the role played by lead in lead silicate glasses but there is still not a complete consensus on the subject [16,17].…”
Section: Introductionmentioning
confidence: 99%